The Polarization of Population Growth on the Development of Micro, Small, and Medium Enterprises in the Medan Tuntungan District - Hardianto Hardianto; Uswatun Hasanah; Rahmad Sembiring (International Forum of Researchers and Lecturers, 2026)
Micro, Small, and Medium Enterprises (MSMEs) have an important role in supporting economic growth and improving people’s income. The development of MSMEs is closely related to population growth and residential settlement patterns, especially in urban areas. This study aims to examine the effect of increasing residential settlements on the development of MSMEs in Medan Tuntungan District. The analysis focuses on the influence of population growth and the number of MSMEs on MSME income, as well as differences in MSME development between densely populated and less populated areas. This research used quantitative descriptive method and multiple linear regression analysis. Primary data are collect through questionnaires and interviews 100 MSME owners in Medan Tuntungan District. Secondary data were obtained from government reports and relevant literature. The independent variables in this study are population growth and the number of MSMEs, while the dependent variable is MSME income. The results show that population growth has positive and significant effect on MSME income. Number of MSMEs also has a positive and significant effect on MSME income. Overall, both variables jointly influence MSME income in Medan Tuntungan District. These findings indicate that the growth of residential settlements can provide opportunities for MSME development when supported by proper government policies and empowerment programs.